Pharmaceutical Aspects of Supply Chain Management - Hattayer, Melinda; Gál, József (Current social and economic processes / Jelenkori Társadalmi és Gazdasági Folyamatok, 2022)
Supply chain management is an outstanding topic in the pharmaceutical industry and regulated by several guidelines. All type of transportation methods have both advantages and disadvantages: decisions usually take into consideration the material / product itself (quality and quantity), time available, price and complexity of the route. The role of other participants (brokers, distributors etc.) is also necessary to be assessed evaluating the risk related to their activity. The most important element for this evaluation is the level of GxP (good practice in drug development) compliance which is interpreted by them based on this we can determine the risk possibly affecting the product safety. Risk reducing actions should be taken in such cases when the calculated RPN numbers are too high, and efficacy of the actions taken has to be reviewed as well. Difficulties due to the COVID-19 pandemic and its consequences may arise larger demand from certain materials which means that the necessity for existence of technical-logistic background agreements are essential in order to realize effective supply of materials.